Analisis Dampak Harga Minyak Dunia terhadap Stabilitas Makroekonomi Indonesia: Pendekatan Vector Autoregression (VAR) - Vonni Cahyani; Sri Maryati; Edi Ariyanto (Jurnal Riset Ekonomi dan Akuntansi, 2025)
This study aims to analyze the impact of world oil prices on Indonesia's macroeconomic stability represented by the BI Rate, the rupiah exchange rate, and inflation during the 2018–2025 period. Fluctuations in world oil prices, acting as a source of external shocks, have the potential to affect the economy through changes in production costs, distribution, and economic activity. The study employs a quantitative approach using monthly time-series data comprising 96 observations. The Vector Autoregression (VAR) method is used to identify dynamic relationships among the variables. The results indicate no long-term relationship between world oil prices, the BI Rate, the rupiah exchange rate, and inflation. VAR estimates suggest that world oil prices do not significantly affect the BI Rate, the rupiah exchange rate, or inflation. Impulse Response Function analysis reveals that the responses of these three variables to world oil price shocks are temporary, with the variables eventually returning to equilibrium. Forecast Error Variance Decomposition results further show that the contribution of world oil prices to explaining variations in the BI Rate, the rupiah exchange rate, and inflation is relatively small. These findings indicate that Indonesia's macroeconomic stability during the study period was influenced more by domestic factors than by fluctuations in world oil prices. The study's results can serve as input for economic policy formulation in the face of global uncertainty.